Radiosensitization by BRAF inhibitors - Strobel, Sophia; Jensen, Alexandra; Enk, Alexander; Hassel, Jessica C. (Journal der Deutschen Dermatologischen Gesellschaft, 2017)
Background Increased skin toxicity during combination therapy with a BRAF inhibitor and radiation therapy has recently been reported. Material and Methods We present seven melanoma patients with non-resectable stage III or IV disease and concomitant treatment with a BRAF inhibitor and radiation therapy. Results In all patients, combination therapy yielded a good local response. Only two patients, both on vemurafenib, showed severe radiation dermatitis (CTCAE grade 3/4) after one and two weeks, respectively, resulting in interruption of BRAF inhibitor treatment. The respective cumulative radiation dose was 10 Gy and 35 Gy. The remaining vemurafenib patients displayed only mild radiation dermatitis CTCAE grade 2; the only dabrafenib patient CTCAE grade 1. In one patient, recall dermatitis was diagnosed 14 days after completion of radiation therapy with a cumulative dose of 30 Gy. Conclusions Severe skin toxicity caused by BRAF inhibitor-induced radiosensitization is not common and usually amenable to treatment. Thus, combination treatment should remain a therapeutic option, especially in melanoma patients characterized by aggressive tumor growth. Although there is an increased risk of skin toxicity during combination therapy, it is usually well tolerated by most patients. Sequential - instead of simultaneous - treatment does not seem to prevent such toxicity reactions.